Perancangan Program Aplikasi Pengelolaan Kas Berbasis Web Pada Perusahaan Jasa Las dan Bubut - Heldalina; Emy Iryanie; Muhammad Syahid Pebriadi; Muhammad Azriel Hidayat (Universitas Sains dan Teknologi Komputer, 2022)
Accounting information systems play an important role in recording a company's transactions. Because it can assist companies in working on their financial reports, so that the resulting data is well organized and can speed up the data processing process. CV. RR Wasilah Teknik is a company engaged in welding and lathe services. The main problem that occurs in this company is that it is still recording transactions manually and using Microsoft excel. This results in the system not running effectively and efficiently. So, it is necessary to make a computerized application. The research method is applied to the research phase such as data collection, system analysis, system design, system implementation, and system testing. The results of the study are cash management applications that help companies record incoming and outgoing cash transactions. This application helps the system running in the company to be more effective and efficient.